BODIES R US: Ethical Views on the Commercialization of the Dead in Medical Education and Research. Issue 3 (21st September 2018) - Champney, Thomas H.; Hildebrandt, Sabine; Gareth Jones, D.; Winkelmann, Andreas
Abstract: With the ongoing and expanding use of willed bodies in medical education and research, there has been a concomitant rise in the need for willed bodies and an increase in the means of supplying these bodies. A relatively recent development to enlarge this supply has been the growth of for‐ profit willed body companies ("body brokers") in the United States. These companies advertise for donors, cover all cremation and other fees for the donor, distribute the bodies or body parts nationally and internationally, and charge their users for access to the body or body parts. In doing so, they generate substantial profits. This review examines the historical development of willed body programs, the legal and economic aspects of willed body programs, and then provides an ethical framework for the use of willed bodies. The ethical principles described include detailed informed consent from the donors, comprehensive and transparent information about the process from the body donation organizations, and societal input on the proper and legal handling of willed bodies. Based on the ethical principles outlined, it is recommended that there be no commercialization or commodification of willed bodies, and that programs that use willed bodies should not generate profit.